PROFITABILITAS, LIKUIDITAS, DAN HARGA SAHAM: STUDI EMPIRIS ATAS INSTRUMEN LQ-45 - Setyoningrum, Eki (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
This research was conducted to determine the effect of profitabilityand liquidity on stock prices. The independent variables used are returnon assets, return on equity, current ratio, and quick ratio. The population inthis study is non-financial LQ-45 companies registered in succession in 2016–2018. This study uses secondary data derived from financial statementsthat can be accessed on the Indonesia Stock Exchange. This research methoduses multiple linear regression analysis. The sampling technique used waspurposive sampling where the samples obtained in the study were 87 companies.The results showed that (1) return on assets has a positive effect onstock prices; (2) return on equity has a negative effect on stock prices; (3)current ratio has no effect on stock prices; (4) quick ratio has a negativeeffect on stock prices. But simultaneously return on assets, return on equity,current ratio, and quick ratio affect the stock price of 37.4%, while theremaining 62.6% comes from other variables that are not contained in thisresearch model.